2021
DOI: 10.7759/cureus.14764
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Progressive Multifocal Leukoencephalopathy in Multiple Sclerosis Patient Treated With Natalizumab: A Systematic Review

Abstract: Natalizumab, a monoclonal antibody acting on alpha4 integrin receptors, is frequently used to treat multiple sclerosis patients. The biggest downside is the risk of development of progressive multifocal leukoencephalopathy, an immune-related condition affecting mainly the central nervous system. The presence of the John Cunningham virus (JCV) and its reactivation is an important factor in the development of progressive multifocal leukoencephalopathy (PML). This study highlights its different proposed mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The long-term studies (Boziki et al, 2021;Butzkueven et al, 2020a;Guger et al, 2021;Prosperini et al, 2017) confirm that natalizumab is a highly effective treatment option for PwMS. Risk stratification for PML and risk management strategies that include patient education and close monitoring have improved outcomes and reduced the number of natalizumab-associated PML incidences (Vivekanandan et al, 2021;Vukusic et al, 2020). With close monitoring, PwMS at high risk for PML may be kept on natalizumab treatment instead of discontinuing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term studies (Boziki et al, 2021;Butzkueven et al, 2020a;Guger et al, 2021;Prosperini et al, 2017) confirm that natalizumab is a highly effective treatment option for PwMS. Risk stratification for PML and risk management strategies that include patient education and close monitoring have improved outcomes and reduced the number of natalizumab-associated PML incidences (Vivekanandan et al, 2021;Vukusic et al, 2020). With close monitoring, PwMS at high risk for PML may be kept on natalizumab treatment instead of discontinuing.…”
Section: Discussionmentioning
confidence: 99%
“…2 is an algorithm for MRI-based PML safety monitoring during natalizumab therapy. As a result of patient education and monitoring strategies, the incidence of natalizumab-associated PML has decreased in recent years (Vivekanandan et al, 2021;Vukusic et al, 2020).…”
Section: Pml Risk Stratification Incorporating the Jcv Indexmentioning
confidence: 99%
“…Indeed, apart from low CD4 þ cell count, the impact of immunosuppressive factors on JCV regulation and reactivation is not well known [32,36]. For example, the occurrence of PML in patients treated with ruxolitinib, a selective Janus kinase inhibitor, despite normal CD4 þ T-cell count, or in patients treated with natalizumab, a humanized IgG4 antibody that does not affect CD4 þ T-cell count, suggests the involvement of other immunological factors [37,38]. Other limitations include the retrospective nature of the study and the small number of cases identified.…”
Section: Discussionmentioning
confidence: 99%